A Critical Study of The Arabic Dictionary: Al-Wasith Dictionary - Hadziq, Muhammad Fadhil; Makfiro, Nikmatul; Fithtriyah, Aidah; Bahruddin, Uril (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Dictionaries plays a significant role as the repository of language, preserving the culture and civilization of peoples through examples and evidence within it. It proves to be an effective tool for learning the Arabic language, especially for non-native speakers. This research Dictionaries come in various forms. They can be categorized based on the number of languages involved: monolingual and bilingual or multilingual. One prominent monolingual Arabic dictionary is the